Pt Modified TiO2–x/C Composites with Metal‐organic Frameworks as Precursors for Photodegradation of Organic Dye. Issue 4 (4th February 2020) - Xu, Qing; Fan, Dongmei; He, Bingbing
Abstract : A series of Pt modified TiO2– x /C composites with higher specific surface area were obtained by using a Zn‐Ti heterometallic metal‐organic framework (MOF) as the precursor. The photocatalytic activities of these composites were studied by methylene blue (MB) as a representative organic pollutant. The chemical composition and porosity of these composites can be adjusted by changing the pyrolysis temperature. Among them, the sample being pyrolyzed at 1000 °C (PTC‐P10) showed excellent photocatalytic performance, and its rate constant of degradation of MB was higher than that of ATC‐P10 (Ag modified TiO2– x /C composites) due to the rapid capture of electrons and the expansion of the photoresponse range caused by Pt modifying. This work represents a novel approach towards Pt modified TiO2– x /C composites as photocatalysts. Abstract :